A kind of antioxidant and antibacterial PBAT degradable film and its preparation method and application
By combining modified calcium carbonate with natural polyphenol compounds, the shortcomings of PBAT composites in antioxidant and antibacterial properties are solved, and their compatibility and performance are improved, achieving the multiple properties of composites while reducing costs.
Patent Information
- Application Number
- CN202311519781.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-11-15
AI Technical Summary
In the prior art, calcium carbonate filled PBAT composite materials fail to impart antioxidant and antibacterial properties while reducing production costs, and the filling of calcium carbonate alone is poor in compatibility with PBAT.
Improve the compatibility and performance of the composite material by mixing natural polyphenol compounds with calcium carbonate, modifying calcium carbonate, and blending it with PBAT, compatibility agent and plasticizer.
It is achieved to improve the mechanical properties, heat resistance, antioxidant properties and antibacterial properties of PBAT composite materials while reducing production costs, forming a versatile antioxidant and antibacterial PBAT degradable film.
Smart Images

Figure BDA0004551568900000111 
Figure BDA0004551568900000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to an antioxidant and antibacterial PBAT degradable film and a preparation method and application thereof. Background Art
[0002] With the improvement of people's living standards, food safety issues have received more and more attention. The development of new, green, safe and environmentally friendly multifunctional food packaging materials has become a hot spot in food packaging research and development. Polybutylene terephthalate-adipate (PBAT) is a copolymer obtained by compounding butylene adipate and butylene terephthalate. It is an aliphatic-aromatic copolyester and a type of biodegradable plastic that is widely used in the current market. Its characteristics are that it can be decomposed and metabolized by a variety of microorganisms and enzymes in animals and plants under natural conditions, and finally degraded into water and carbon dioxide, without causing environmental pollution. Compared with traditional petroleum-based polymers, the production and use of PBAT can effectively alleviate the pressure caused by the depletion of petrochemical resources and greatly reduce the "white pollution" caused by traditional plastic packaging waste. The PBAT molecular chain segment has the flexibility of aliphatic and the rigidity of aromatic. The aliphatic segment gives it a certain toughness, ductility and high elongation at break, while the rigidity of aromatic gives it good thermal stability. Therefore, PBAT film materials are widely used in fresh-keeping packaging, food antibacterial packaging and pharmaceutical packaging. However, compared with traditional materials, PBAT is expensive, two to three times the price of polyethylene materials with comparable mechanical properties, and its tensile strength and thermodynamic properties are also insufficient. Moreover, the application of PBAT in food packaging also requires it to have antioxidant and antibacterial properties, but PBAT itself does not have antioxidant and antibacterial properties, which greatly limits the application of this biodegradable plastic in the above fields.
[0003] Inorganic non-metallic powders such as calcium carbonate and montmorillonite can effectively reduce the production cost of composite materials because of their wide sources, low prices, and the ability to improve the stability and heat resistance of related composite materials. Studies have shown that filling PBAT with calcium carbonate can maintain or even enhance its mechanical properties such as tensile strength and elongation at break and significantly improve its crystallinity (Reference 1. Yang, Y.; Zhang, C.; Weng, Y., Effects of CaCO 3 surfacemodification and water spraying on the weatheringproperties ofPBAT / CaCO 3films.Polym.Test.2021,102; Document 2. Shang, J.; Li, C.; Song, Y.; Yan, M.; Li, L.; Hu, C., Gas-solid fluidization modification of calcium carbonate for high-performance poly(butylene adipate-co-terephthalate)(PBAT) composites. Front Chem 2022, 10, 1119978). Chinese patent CN 113652063 A discloses a calcium carbonate-filled PBAT / PLA degradable film and a preparation method thereof, which is prepared from the following raw materials in parts by weight: 50-80 parts of PBAT, 5-15 parts of PLA, 20-40 parts of nano calcium carbonate, 1-3 parts of surface modifier, 0.3-1 part of chain extender, 0.1-1 part of lubricant, 0.2-1 part of opening agent, and 0.1-1 part of antioxidant. The method reduces the amount of PBAT and PLA by adding nano calcium carbonate, thereby reducing production costs; and the addition of nano calcium carbonate improves the stability and heat resistance of the film and improves the processing performance and mechanical properties. Chinese patent CN 113801350A also discloses a calcium carbonate filled PBAT / PLA biodegradable plastic film and a preparation method thereof. The method melt blends polybutylene terephthalate-adipate-butylene glycol, polylactic acid, calcium carbonate powder, compatibilizer A and additives to obtain a film with good mechanical properties, with a transverse tensile strength of 15.3-20.2MPa, a transverse elongation at break of 497.1-614.2%, a longitudinal tensile strength of 20.4-24.4MPa, a longitudinal elongation at break of 390.4-460.7%, and a heat sealing strength of 22.8-24.7N / 15mm, all of which illustrate the advantages of calcium carbonate in reducing costs and improving the performance of composite materials.
[0004] However, it can be found that under the existing technology, calcium carbonate filling does not give the composite material antioxidant and antibacterial properties while reducing the production cost of the composite material, and the compatibility of calcium carbonate filling alone with PBAT is poor. It is necessary to add a variety of additives to improve the dispersion of calcium carbonate in the matrix, thereby improving the bonding ability with the matrix.
[0005] Therefore, the study of a preparation method that can improve the filling of calcium carbonate and make the PBAT composite material have antioxidant and antibacterial properties is of great significance to the application and promotion of PBAT in the field of food packaging. Summary of the invention
[0006] In view of this, the present invention provides an antioxidant and antibacterial PBAT degradable film and a preparation method thereof, the purpose of which is to make the PBAT degradable film have antioxidant and antibacterial properties while reducing costs.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides an antioxidant and antibacterial PBAT degradable film, comprising the following raw materials in parts by weight: 60 to 95 parts of polybutylene terephthalate-adipate, 5 to 30 parts of calcium carbonate, 0.5 to 5 parts of natural polyphenol compounds, 0.3 to 5 parts of compatibilizers and 0.1 to 1 parts of plasticizers.
[0009] Preferably, the melt index of the polybutylene terephthalate-adipate is less than or equal to 5 g / 10 min, and the particle size of the calcium carbonate is 2000-4000 mesh.
[0010] Preferably, the natural polyphenol compound is one or more of gallic acid, chlorogenic acid and baicalin.
[0011] Preferably, the compatibilizer is maleic anhydride grafted polybutylene terephthalate-adipate and / or glycidyl methacrylate grafted polybutylene terephthalate-adipate.
[0012] Preferably, the plasticizer is one or more of tributyl citrate, diisononyl phthalate and epoxidized soybean oil.
[0013] The present invention also provides a method for preparing the antioxidant and antibacterial PBAT degradable film, comprising the following steps:
[0014] (1) mixing calcium carbonate with a natural polyphenol compound solution and reacting the mixture to obtain modified calcium carbonate;
[0015] (2) mixing modified calcium carbonate, polybutylene terephthalate-adipate, a compatibilizer and a plasticizer, and then extruding and granulating the mixture to obtain granules;
[0016] (3) After the particles are blown into film, a PBAT degradable film is obtained;
[0017] The solvent of the natural polyphenol compound solution in step (1) is one or more of acetone, ether and N,N-dimethylformamide.
[0018] Preferably, in step (1), the mixing temperature is 70-90° C., the mixing time is 1-2 h, the reaction temperature is 150-170° C., and the reaction time is 10-30 min.
[0019] Preferably, the mixing temperature in step (2) is 40-60°C, the extrusion granulation temperature is 150-170°C, the extrusion granulation speed is 220-380rpm, the extrusion granulation feeding speed is 25-35rpm, and the melt pressure of the extrusion granulation is 5-10MPa.
[0020] Preferably, the temperature of the film blowing in step (3) is 155-170°C.
[0021] The present invention also provides the use of the antioxidant and antibacterial PBAT degradable film in food packaging.
[0022] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:
[0023] The present invention utilizes the structural properties of natural polyphenol compounds that have both polyphenols and carboxyl groups, modifies calcium carbonate through natural polyphenol compounds, and uses a compatibilizer to eliminate the alcoholic hydroxyl groups carried by the natural polyphenol compounds themselves, and then blends with PBAT to improve the compatibility of PBAT and calcium carbonate powder, thereby reducing production costs while improving the mechanical properties and heat resistance of the composite film, and also introducing a polyphenol structure to make the composite film have good antioxidant and antibacterial properties. The polyphenol compounds used in the present invention are natural medicinal material extraction components, which are non-toxic and harmless, and can be completely degraded with PBAT, with zero pollution. The present invention utilizes the structural characteristics and functional characteristics of polyphenol compounds, and obtains a PBAT degradable film with excellent mechanical properties, good heat resistance and antioxidant and antibacterial properties through a simple extrusion preparation process. DETAILED DESCRIPTION
[0024] The present invention provides an antioxidant and antibacterial PBAT degradable film, comprising the following raw materials in parts by weight: 60 to 95 parts of polybutylene terephthalate-adipate, 5 to 30 parts of calcium carbonate, 0.5 to 5 parts of natural polyphenol compounds, 0.3 to 5 parts of compatibilizers and 0.1 to 1 parts of plasticizers.
[0025] In the present invention, the mass fraction of the polybutylene terephthalate-adipate is 60 to 95 parts, preferably 65 to 90 parts, and more preferably 70 to 80 parts.
[0026] In the present invention, the melt index of the polybutylene terephthalate-adipate is preferably less than or equal to 5 g / 10 min, more preferably 1 to 4 g / 10 min, and even more preferably 2 to 3 g / 10 min.
[0027] In the present invention, the mass fraction of the calcium carbonate is 5 to 30 parts, preferably 10 to 25 parts, and more preferably 15 to 20 parts.
[0028] In the present invention, the particle size of the calcium carbonate is preferably 2000-4000 mesh, more preferably 2500-3500 mesh, and more preferably 2800-3200 mesh.
[0029] In the present invention, the mass fraction of the natural polyphenol compound is 0.5 to 5 parts, preferably 1 to 4 parts, and more preferably 2 to 3 parts.
[0030] In the present invention, the natural polyphenol compound is preferably one or more of gallic acid, chlorogenic acid and baicalin.
[0031] In the present invention, the natural polyphenol compound is preferably a natural medicinal material extract, which is non-toxic and harmless, has a polyphenol structure, and has antioxidant and antibacterial properties.
[0032] In the present invention, the natural polyphenol compound is first mixed with calcium carbonate powder, and its carboxyl group is adsorbed on the surface of calcium carbonate particles to obtain natural polyphenol compound modified calcium carbonate powder, thereby reducing the hydrophilicity of calcium carbonate; the polyphenol structure introduced into the natural polyphenol compound modified calcium carbonate can also make the composite material have better antioxidant and antibacterial properties.
[0033] In the present invention, the mass fraction of the compatibilizer is 0.3 to 5 parts, preferably 0.8 to 4.2 parts, and more preferably 1.2 to 2.8 parts.
[0034] In the present invention, the compatibilizer is preferably maleic anhydride grafted polybutylene terephthalate-adipate and / or glycidyl methacrylate grafted polybutylene terephthalate-adipate.
[0035] In the present invention, the compatibilizer further reduces the number of alcoholic hydroxyl groups in the natural polyphenol compound, improves the hydrophobicity of the modified calcium carbonate powder as a whole, enables it to obtain better compatibility when blended with PBAT, thereby increasing the addition amount of calcium carbonate powder, reducing production costs, and improving the mechanical properties and heat resistance of the PBAT composite material.
[0036] In the present invention, the mass fraction of the plasticizer is 0.1 to 1 part, preferably 0.4 to 0.8 part, and more preferably 0.5 to 0.7 part.
[0037] In the present invention, the plasticizer is preferably one or more of tributyl citrate, diisononyl phthalate and epoxidized soybean oil.
[0038] The present invention also provides a method for preparing the antioxidant and antibacterial PBAT degradable film, comprising the following steps:
[0039] (1) mixing calcium carbonate with a natural polyphenol compound solution and reacting the mixture to obtain modified calcium carbonate;
[0040] (2) mixing modified calcium carbonate, polybutylene terephthalate-adipate, a compatibilizer and a plasticizer, and then extruding and granulating the mixture to obtain granules;
[0041] (3) After the particles are blown into film, a PBAT degradable film is obtained;
[0042] The solvent of the natural polyphenol compound solution in step (1) is one or more of acetone, ether and N,N-dimethylformamide; when the natural polyphenol compound is baicalin, the solvent is preferably N,N-dimethylformamide, when the natural polyphenol compound is gallic acid, the solvent is preferably acetone and / or ether, and when the natural polyphenol compound is chlorogenic acid, the solvent is preferably acetone.
[0043] In the present invention, the preparation method of the antioxidant and antibacterial PBAT degradable film firstly uses natural polyphenol compounds to treat calcium carbonate, reduce the polarity of the surface of calcium carbonate, and promote the compatibility of calcium carbonate when mixed with the PBAT matrix; however, since the natural polyphenol compounds have an alcohol hydroxyl structure, maleic anhydride grafted polybutylene terephthalate-adipate (MAH-g-PBAT) or glycidyl methacrylate grafted polybutylene terephthalate-adipate (GMA-g-PBAT) compatibilizer is added when the modified calcium carbonate and PBAT are melt-blended, and the anhydride groups therein are reacted with hydroxyl groups to generate polyester compounds, further eliminating the hydroxyl structure, and at the same time, a plasticizer is added to ensure that the calcium carbonate can be well mixed with the PBAT, increase the filling amount of calcium carbonate and improve the mechanical and thermodynamic properties of the composite material.
[0044] In the present invention, the calcium carbonate is dried before being mixed with the natural polyphenol compound solution. The drying time is preferably 6 to 10 hours, more preferably 7 to 9 hours, and more preferably 8 hours. The drying temperature is preferably 70 to 90° C., more preferably 74 to 86° C., and more preferably 76 to 82° C.
[0045] In the present invention, the mixing temperature in step (1) is preferably 70-90°C, more preferably 73-87°C, more preferably 78-82°C, the mixing time is preferably 1-2h, more preferably 80-110min, more preferably 85-105min, the reaction temperature is preferably 150-170°C, more preferably 155-165°C, more preferably 158-162°C, the reaction time is preferably 10-30min, more preferably 16-28min, more preferably 22-24min.
[0046] In the present invention, the mixing temperature in step (2) is preferably 40-60°C, more preferably 45-55°C, more preferably 48-52°C, the mixing time is preferably 10-20min, more preferably 12-18min, more preferably 14-16min, the extrusion granulation temperature is preferably 150-170°C, more preferably 154-167°C, more preferably 158-162°C, the extrusion granulation speed is preferably 220-380rpm, more preferably 250-360rpm, more preferably 280-320rpm, the feeding speed of extrusion granulation is preferably 25-35rpm, more preferably 28-33rpm, more preferably 30-31rpm, and the melt pressure of extrusion granulation is preferably 5-10MPa, more preferably 6-9MPa, more preferably 7-8MPa.
[0047] In the present invention, the temperature of the film blowing in step (3) is preferably 155-170°C, more preferably 158-166°C, and even more preferably 160-162°C.
[0048] The present invention also provides the use of the antioxidant and antibacterial PBAT degradable film in food packaging.
[0049] In the present invention, the food packaging is preferably a plastic wrap, a food bag or a fast food box.
[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0051] In Examples 1 to 8 and Comparative Example 1, the extrusion granulation is carried out in a twin-screw extruder, and the temperature of the twin-screw extruder is set as follows: 160°C in zone 1, 160°C in zone 2, 160°C in zone 3, 155°C in zone 4, 155°C in zone 5, 155°C in zone 6, 150°C in zone 7, 150°C in zone 8, 150°C in zone 9, 165°C in zone 10, and 165°C in the die head.
[0052] Example 1
[0053] The antioxidant and antibacterial PBAT degradable film is prepared from the following raw materials in parts by weight: 85 parts of PBAT, 10 parts of calcium carbonate, 0.5 parts of baicalin, 5 parts of MAH-g-PBAT and 0.5 parts of tributyl citrate.
[0054] Weigh 10 parts of 2800 mesh calcium carbonate and dry them at 80°C for 8 hours to eliminate the moisture therein, dissolve 0.5 parts of baicalin with N,N-dimethylformamide to form a baicalin solution with a concentration of 0.25 g / mL, then add the baicalin solution and dried calcium carbonate into a high-speed stirrer at a speed of 650 rpm, stir at 80°C for 1 hour, then heat to 160°C and continue stirring for 15 minutes, and cool to obtain calcium carbonate modified with baicalin.
[0055] The obtained modified calcium carbonate, 85 parts of PBAT, 5 parts of MAH-g-PBAT and 0.5 parts of tributyl citrate were added to a high mixer and stirred at 900 rpm for 15 minutes at 40°C, and the material was discharged; the obtained material was added to a twin-screw extruder granulator for melt extrusion, and granules were obtained after cooling. The main speed of the twin-screw extruder was set to 300 rpm, the feed speed was 25 rpm, and the melt pressure was 6 MPa.
[0056] The obtained particles were put into a film blowing test machine for film blowing, and the temperature of the heating zone of the film blowing test machine was 160° C. to obtain a PBAT degradable film.
[0057] Example 2
[0058] The antioxidant and antibacterial PBAT degradable film is prepared from the following raw materials in parts by weight: 80 parts of PBAT, 15 parts of calcium carbonate, 1 part of gallic acid, 5 parts of GMA-g-PBAT and 0.5 parts of diisononyl phthalate.
[0059] Weigh 15 parts of 3000 mesh calcium carbonate and dry them at 85°C for 7 hours to eliminate the moisture therein, dissolve 1 part of gallic acid with acetone to form a gallic acid solution with a concentration of 0.25 g / mL, then add the prepared gallic acid solution and dried calcium carbonate respectively into a high-speed mixer at a speed of 680 rpm, stir at 85°C for 2 hours, then heat to 155°C and continue stirring for 20 minutes, and cool to obtain calcium carbonate modified with gallic acid.
[0060] The obtained modified calcium carbonate, 80 parts of PBAT, 5 parts of GMA-g-PBAT and 0.5 parts of diisononyl phthalate were added into a high mixer and stirred at 980 rpm for 16 min at 50° C., and the material was discharged; the obtained material was added into a twin-screw extruder granulator for melt extrusion, and granules were obtained after cooling. The main speed of the twin-screw extruder was set to 350 rpm, the feeding speed was 30 rpm, and the melt pressure was 7 MPa.
[0061] The obtained particles were put into a film blowing test machine for film blowing. The temperature of the heating zone of the film blowing test machine was 155° C. to obtain a PBAT degradable film.
[0062] Example 3
[0063] The antioxidant and antibacterial PBAT degradable film is prepared from the following raw materials in parts by weight: 75 parts of PBAT, 20 parts of calcium carbonate, 2.5 parts of chlorogenic acid, 5 parts of GMA-g-PBAT and 0.5 parts of epoxidized soybean oil.
[0064] Weigh 20 parts of 3500 mesh calcium carbonate and dry them at 85°C for 7 hours to eliminate the moisture therein. Dissolve 2.5 parts of chlorogenic acid with acetone to form a chlorogenic acid solution with a concentration of 0.25 g / mL. Then add the prepared chlorogenic acid solution and dried calcium carbonate respectively into a high-speed mixer at a speed of 700 rpm, stir at 75°C for 2 hours, then heat to 170°C and continue stirring for 15 minutes, and cool to obtain calcium carbonate modified with chlorogenic acid.
[0065] The modified calcium carbonate obtained was added into a high mixer together with 75 parts of PBAT, 5 parts of GMA-g-PBAT and 0.5 parts of epoxidized soybean oil, and stirred at 880 rpm for 18 min at 55° C., and the material was discharged; the obtained material was added into a twin-screw extruder granulator for melt extrusion, and granules were obtained after cooling. The main speed of the twin-screw extruder was set to 270 rpm, the feeding speed was 28 rpm, and the melt pressure was 8 MPa.
[0066] The obtained particles were put into a film blowing test machine for film blowing, and the temperature of the heating zone of the film blowing test machine was 160° C. to obtain a PBAT degradable film.
[0067] Example 4
[0068] The antioxidant and antibacterial PBAT degradable film is prepared from the following raw materials in parts by weight: 65 parts of PBAT, 25 parts of calcium carbonate, 5 parts of baicalin, 5 parts of GMA-g-PBAT and 0.5 parts of epoxidized soybean oil.
[0069] Weigh 25 parts of 2800 mesh calcium carbonate and dry them at 80°C for 8 hours to eliminate the moisture therein, dissolve 5 parts of baicalin with N,N-dimethylformamide to form a baicalin solution with a concentration of 0.25 g / mL, then add the prepared baicalin solution and dry calcium carbonate respectively into a high-speed mixer at a speed of 580 rpm, stir at 80°C for 1 hour, then heat to 160°C and continue stirring for 15 minutes, and cool to obtain calcium carbonate modified with baicalin.
[0070] The modified calcium carbonate obtained was added into a high mixer together with 65 parts of PBAT, 5 parts of GMA-g-PBAT and 0.5 parts of epoxidized soybean oil, and stirred at 900 rpm for 15 min at 55° C., and the material was discharged; the obtained material was added into a twin-screw extruder granulator for melt extrusion, and granules were obtained after cooling. The main speed of the twin-screw extruder was set to 300 rpm, the feeding speed was 25 rpm, and the melt pressure was 6 MPa.
[0071] The obtained particles were put into a film blowing test machine for film blowing, and the temperature of the heating zone of the film blowing test machine was 160° C. to obtain a PBAT degradable film.
[0072] Example 5
[0073] The antioxidant and antibacterial PBAT degradable film is prepared from the following raw materials in parts by weight: 60 parts of PBAT, 30 parts of calcium carbonate, 5 parts of gallic acid, 5 parts of GMA-g-PBAT and 0.5 parts of diisononyl phthalate.
[0074] Weigh 30 parts of 3000 mesh calcium carbonate and dry them at 85°C for 7 hours to eliminate the moisture therein, dissolve 5 parts of gallic acid with ether to form a gallic acid solution with a concentration of 0.25 g / mL, then add the prepared gallic acid solution and dried calcium carbonate respectively into a high-speed mixer at a speed of 500 rpm, stir at 85°C for 2 hours, then heat to 155°C and continue stirring for 20 minutes, and cool to obtain calcium carbonate modified with gallic acid.
[0075] The obtained modified calcium carbonate, 60 parts of PBAT, 5 parts of GMA-g-PBAT and 0.5 parts of diisononyl phthalate were added into a high mixer and stirred at 50°C at a speed of 1000 rpm for 10 minutes, and the material was discharged; the obtained material was added into a twin-screw extruder granulator for melt extrusion, and granules were obtained after cooling. The main speed of the twin-screw extruder was set to 350 rpm, the feeding speed was 30 rpm, and the melt pressure was 7 MPa.
[0076] The obtained particles were put into a film blowing test machine for film blowing. The temperature of the heating zone of the film blowing test machine was 155° C. to obtain a PBAT degradable film.
[0077] Example 6
[0078] The antioxidant and antibacterial PBAT degradable film is prepared from the following raw materials in parts by weight: 70 parts of PBAT, 20 parts of calcium carbonate, 5 parts of baicalin, 5 parts of GMA-g-PBAT and 0.5 parts of diisononyl phthalate.
[0079] Weigh 20 parts of 2800 mesh calcium carbonate and dry them at 85°C for 8 hours to eliminate the moisture therein. Dissolve 5 parts of baicalin with N,N-dimethylformamide to form a baicalin solution with a concentration of 0.25 g / mL. Then add the prepared baicalin solution and dried calcium carbonate respectively into a high-speed mixer at a speed of 500 rpm, stir at 85°C for 2 hours, then heat to 155°C and continue stirring for 20 minutes, and cool to obtain calcium carbonate modified with baicalin.
[0080] The obtained modified calcium carbonate, 70 parts of PBAT, 5 parts of GMA-g-PBAT and 0.5 parts of diisononyl phthalate were added into a high mixer and stirred at 50°C and 980 speed for 14 minutes, and the material was discharged; the obtained material was added into a twin-screw extruder granulator for melt extrusion, and granules were obtained after cooling. The main speed of the twin-screw extruder was set to 350rpm, the feeding speed was 30rpm, and the melt pressure was 7MPa.
[0081] The obtained particles were put into a film blowing test machine for film blowing. The temperature of the heating zone of the film blowing test machine was 155° C. to obtain a PBAT degradable film.
[0082] Example 7
[0083] The antioxidant and antibacterial PBAT degradable film is prepared from the following raw materials in parts by weight: 75 parts of PBAT, 20 parts of calcium carbonate, 1 part of chlorogenic acid, 5 parts of GMA-g-PBAT and 0.5 parts of epoxidized soybean oil.
[0084] Weigh 20 parts of 3500 mesh calcium carbonate and dry them at 85°C for 7 hours to eliminate the moisture therein. Dissolve 1 part of chlorogenic acid with acetone to form a chlorogenic acid solution with a concentration of 0.25 g / mL. Then add the prepared chlorogenic acid solution and dried calcium carbonate respectively into a high-speed mixer at a speed of 550 rpm, stir at 75°C for 2 hours, then heat to 170°C and continue stirring for 15 minutes, and cool to obtain calcium carbonate modified with chlorogenic acid.
[0085] The modified calcium carbonate obtained was added into a high mixer together with 75 parts of PBAT, 5 parts of GMA-g-PBAT and 0.5 parts of epoxidized soybean oil, and stirred at 880 rpm for 16 min at 55° C., and the material was discharged; the obtained material was added into a twin-screw extruder granulator for melt extrusion, and granules were obtained after cooling. The main speed of the twin-screw extruder was set to 270 rpm, the feed speed was 28 rpm, and the melt pressure was 8 MPa.
[0086] The obtained particles were put into a film blowing test machine for film blowing, and the temperature of the heating zone of the film blowing test machine was 160° C. to obtain a PBAT degradable film.
[0087] Example 8
[0088] The antioxidant and antibacterial PBAT degradable film is prepared from the following raw materials in parts by weight: 75 parts of PBAT, 20 parts of calcium carbonate, 0.5 parts of baicalin, 5 parts of MAH-g-PBAT and 0.5 parts of tributyl citrate.
[0089] Weigh 20 parts of 2800 mesh calcium carbonate and dry them at 80°C for 8 hours to eliminate the moisture therein, dissolve 0.5 parts of baicalin with N,N-dimethylformamide to form a baicalin solution with a concentration of 0.25 g / mL, then add the prepared baicalin solution and dried calcium carbonate into a high-speed mixer at a speed of 700 rpm, stir at 80°C for 1 hour, then heat to 160°C and continue stirring for 15 minutes, and cool to obtain calcium carbonate modified with baicalin.
[0090] The obtained modified calcium carbonate, 75 parts of PBAT, 5 parts of MAH-g-PBAT and 0.5 parts of tributyl citrate were added to a high mixer and stirred at 800 rpm for 20 minutes at 40°C, and the material was discharged; the obtained material was added to a twin-screw extruder granulator for melt extrusion, and granules were obtained after cooling. The main speed of the twin-screw extruder was set to 300 rpm, the feeding speed was 25 rpm, and the melt pressure was 6 MPa.
[0091] The obtained particles were put into a film blowing test machine for film blowing, and the temperature of the heating zone of the film blowing test machine was 160° C. to obtain a PBAT degradable film.
[0092] Comparative Example 1
[0093] The antioxidant and antibacterial PBAT degradable film is prepared from the following raw materials in parts by weight: 70 parts of PBAT, 20 parts of calcium carbonate, 5 parts of baicalin, 5 parts of MAH-g-PBAT and 0.5 parts of tributyl citrate.
[0094] Weigh 20 parts of 2800 mesh calcium carbonate and dry them at 80°C for 8 hours to eliminate the moisture therein, and dissolve 0.5 parts of baicalin with N,N-dimethylformamide to form a baicalin solution with a concentration of 0.25 g / mL.
[0095] Dried calcium carbonate, baicalin solution, 70 parts of PBAT, 5 parts of MAH-g-PBAT, and 0.5 parts of tributyl citrate were added to a high mixer and stirred at 900 rpm for 15 minutes at 40°C, and the materials were discharged; the obtained materials were added to a twin-screw extruder granulator for melt extrusion, and granules were obtained after cooling. The main speed of the twin-screw extruder was set to 300 rpm, the feed speed was 25 rpm, and the melt pressure was 6 MPa.
[0096] The obtained particles were put into a film blowing test machine for film blowing, and the temperature of the heating zone of the film blowing test machine was 160° C. to obtain a PBAT degradable film.
[0097] The performance tests were performed on the PBAT degradable films and pure PBAT films obtained in Examples 1 to 8 and Comparative Example 1 respectively:
[0098] (1) Mechanical properties test: The tensile strength and elongation at break of the PBAT degradable films obtained in Examples 1 to 8 and Comparative Example 1 and the pure PBAT film were tested according to GB / T 1040.3-2006 standard, and the tensile speed was 50 mm / min±10%.
[0099] (2) Heat resistance test: The melting temperature and crystallization temperature of the PBAT degradable films obtained in Examples 1 to 8 and Comparative Example 1 and the pure PBAT film were tested according to GB / T 19466.2-2004.
[0100] (3) Antioxidant performance test: The antioxidant properties of the PBAT degradable films obtained in Examples 1 to 8 and Comparative Example 1 and the pure PBAT film were characterized and measured by DPPH free radical scavenging rate.
[0101] (4) Antibacterial performance test: The antibacterial properties of the PBAT degradable films obtained in Examples 1 to 8 and Comparative Example 1 and the pure PBAT film were determined according to the standard GB / T 20944.1-2007 by evaluating the in vitro antibacterial activity of E. coli using the agar diffusion method.
[0102] The test results are shown in Table 1:
[0103] Table 1 Performance test results of PBAT degradable film and pure PBAT film
[0104]
[0105]
[0106] As shown in Table 1, compared with the pure PBAT film, the tensile strength of the PBAT degradable film obtained in Examples 1 to 8 gradually increases with the addition of calcium carbonate modified with natural polyphenol compounds, and reaches a maximum value when the calcium carbonate filling amount is 20 parts. When the content of calcium carbonate continues to increase, its tensile strength gradually decreases, but it is still higher than that of the pure PBAT film. When the filling amount of calcium carbonate is 20 parts, the tensile strength of the PBAT degradable film obtained by the present invention increases with the increase of the content of natural polyphenol compounds, indicating that the modification of calcium carbonate by natural polyphenol compounds enhances the compatibility of calcium carbonate with the PBAT matrix. The change in the elongation at break of the PBAT degradable film is opposite to the change in tensile strength, and its value is gradually decreasing, but when the content of modified calcium carbonate is 20 parts, the elongation at break of the PBAT degradable film obtained by the present invention is only reduced by 12%. In terms of heat resistance, the melting temperature and crystallization temperature of the PBAT degradable film gradually increase with the increase of modified calcium carbonate content, and continue to increase with the increase of natural polyphenol compound content, indicating that the heat resistance of the PBAT degradable film obtained by the present invention is significantly improved compared with the pure PBAT film; in terms of anti-oxidation and antibacterial, the change law of the free radical scavenging rate and antibacterial rate data of the PBAT degradable film is similar to the thermodynamic data, indicating that the PBAT degradable film obtained by the present invention has better and better anti-oxidation and antibacterial properties than the pure PBAT film.
[0107] Compared with the PBAT degradable film obtained in Comparative Example 1, when the calcium carbonate powder is directly melt-blended with PBAT, a compatibilizer and a plasticizer without the modification step of the natural polyphenol compound, its mechanical properties and heat resistance are poor, but the antioxidant and antibacterial properties are not greatly affected. This is consistent with the fact that the antioxidant and antibacterial properties of the PBAT degradable film are mainly brought by the antioxidant and antibacterial properties of the polyphenol compound itself.
[0108] Therefore, based on the above test data, it can be found that by blending natural polyphenol compound-modified calcium carbonate with PBAT, a PBAT biodegradable film with excellent mechanical properties and good antioxidant and antibacterial properties can be prepared.
[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An antioxidant and antibacterial PBAT degradable film, characterized in that: The invention comprises the following raw materials in parts by weight: 60-95 parts of polybutylene terephthalate-adipate, 5-30 parts of calcium carbonate, 0.5-5 parts of natural polyphenol compound, 0.3-5 parts of compatibilizer and 0.1-1 parts of plasticizer; The natural polyphenol compound is one or more of gallic acid, chlorogenic acid and baicalin; The compatibilizer is maleic anhydride grafted polybutylene terephthalate-adipate and / or glycidyl methacrylate grafted polybutylene terephthalate-adipate; The plasticizer is one or more of tributyl citrate, diisononyl phthalate and epoxidized soybean oil; The method for preparing the antioxidant and antibacterial PBAT degradable film comprises the following steps: (1) mixing calcium carbonate with a natural polyphenol compound solution and reacting the mixture to obtain modified calcium carbonate; (2) mixing modified calcium carbonate, polybutylene terephthalate-adipate, a compatibilizer and a plasticizer, and then extruding and granulating the mixture to obtain granules; (3) After the particles are blown into film, a PBAT biodegradable film is obtained.
2. The antioxidant and antibacterial PBAT degradable film according to claim 1, characterized in that: The melt index of the polybutylene terephthalate-adipate is less than or equal to 5g / 10min, and the particle size of the calcium carbonate is 2000-4000 mesh.
3. The method for preparing the antioxidant and antibacterial PBAT degradable film according to any one of claims 1 to 2, characterized in that: The steps include: (1) mixing calcium carbonate with a natural polyphenol compound solution and reacting the mixture to obtain modified calcium carbonate; (2) mixing modified calcium carbonate, polybutylene terephthalate-adipate, a compatibilizer and a plasticizer, and then extruding and granulating the mixture to obtain granules; (3) After the particles are blown into film, a PBAT degradable film is obtained; The solvent of the natural polyphenol compound solution in step (1) is one or more of acetone, ether and N,N-dimethylformamide; The natural polyphenol compound is one or more of gallic acid, chlorogenic acid and baicalin; The compatibilizer is maleic anhydride grafted polybutylene terephthalate-adipate and / or glycidyl methacrylate grafted polybutylene terephthalate-adipate; The plasticizer is one or more of tributyl citrate, diisononyl phthalate and epoxidized soybean oil.
4. The method for preparing the antioxidant and antibacterial PBAT degradable film according to claim 3, characterized in that: In step (1), the mixing temperature is 70-90° C., the mixing time is 1-2 h, the reaction temperature is 150-170° C., and the reaction time is 10-30 min.
5. The method for preparing the antioxidant and antibacterial PBAT degradable film according to claim 3, characterized in that: The mixing temperature in step (2) is 40-60° C., the extrusion granulation temperature is 150-170° C., the extrusion granulation speed is 220-380 rpm, the extrusion granulation feeding speed is 25-35 rpm, and the extrusion granulation melt pressure is 5-10 MPa.
6. The method for preparing the antioxidant and antibacterial PBAT degradable film according to claim 3, characterized in that: The temperature of the film blowing in step (3) is 155-170°C.
7. Use of the antioxidant and antibacterial PBAT degradable film according to any one of claims 1 to 2 in food packaging.
Citation Information
Patent Citations
Calcium carbonate filled PBAT / PLA degradable film and preparation method thereof
CN113652063A
Calcium carbonate filled PBAT / PLA biodegradable plastic film and preparation method thereof
CN113801350A
Antibacterial full-degradable plastic material and preparation method thereof
CN114621563A
Low cost bio-based full degradable film and preparation method thereof
US20200291225A1